Analysis of traffic noise and management of community noise in Malaysia: a case study - Mohd Jailani Mohd Nor,; Fadzlita Mohd Tamiri, (Environmental Management Society, Malaysia, 2002)
Noise can cause annoyance and interfere with daily human activities, and thus may also cause health disorder. In most environmental noise analysis study in Malaysia, the dominant noise source is due to local traffic condition. This paper presents the result of a study on traffic noise and also noise exposure to community in public areas. This research is done using two different approaches, noise level measurement at chosen stations and also questionnaires distribution to respondents in the research areas. If reflects the level of noise pollution in Malaysia and the result from this study can be used to propose legislation and future policies for managing noise problem in Malaysia